Aberrant crosstalk between insulin signaling and mTOR in young Down syndrome individuals revealed by neuronal‐derived extracellular vesicles. Issue 8 (23rd November 2021) - Perluigi, Marzia; Picca, Anna; Montanari, Elita; Calvani, Riccardo; Marini, Federico; Matassa, Roberto; Tramutola, Antonella; Villani, Alberto; Familiari, Giuseppe; Domenico, Fabio Di; Butterfield, D. Allan; Oh, Kenneth J.; et al.
Abstract: Introduction: Intellectual disability, accelerated aging, and early‐onset Alzheimer‐like neurodegeneration are key brain pathological features of Down syndrome (DS). Although growing research aims at the identification of molecular pathways underlying the aging trajectory of DS population, data on infants and adolescents with DS are missing. Methods: Neuronal‐derived extracellular vesicles (nEVs) were isolated form healthy donors (HDs, n = 17) and DS children (n = 18) from 2 to 17 years of age and nEV content was interrogated for markers of insulin/mTOR pathways. Results: nEVs isolated from DS children were characterized by a significant increase in pIRS1 Ser636, a marker of insulin resistance, and the hyperactivation of the Akt/mTOR/p70S6K axis downstream from IRS1, likely driven by the higher inhibition of Phosphatase and tensin homolog (PTEN). High levels of pGSK3β Ser9 were also found. Conclusions: The alteration of the insulin‐signaling/mTOR pathways represents an early event in DS brain and likely contributes to the cerebral dysfunction and intellectual disability observed in this unique population.